Synthesis, characterization, and crystal structure of 2-(2-azidophenyl)-3-oxo-3H-indole 1-oxide - Pawan Dhote; Srinu Tothadi; Chepuri V. Ramana (Acta Crystallographica Section E: Crystallographic Communications, 2024)
An attempt to explore the reactivity of the nitro group in the presence of gold catalysis in comparison to the azide group yielded intriguing results. Surprisingly, only the nitro group exhibited reactivity, ultimately giving rise to the formation of the title isatogen, C14H8N4O2. In the crystal structure, weak C—H...O hydrogen bonds and π–π stacking interactions link the molecules. The structure exhibits disorder of the molecule.